2017
DOI: 10.1016/j.disc.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of signed graph and edge-coloured graph homomorphisms

Abstract: We study homomorphism problems of signed graphs from a computational point of view. A signed graph (G, Σ) is a graph G where each edge is given a sign, positive or negative; Σ ⊆ E(G) denotes the set of negative edges. Thus, (G, Σ) is a 2-edge-coloured graph with the property that the edge-colours, {+, −}, form a group under multiplication. Central to the study of signed graphs is the operation of switching at a vertex, that results in changing the sign of each incident edge. We study two types of homomorphisms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 25 publications
(62 reference statements)
1
64
0
Order By: Relevance
“…Extending the Hell-Nešetřil dichotomy [27] for Hom(H) for 1-edge-coloured graph problems, a complexity dichotomy for s-Hom(H) problems was proved in the papers [7,10]. The authors showed that if the s-core of a signed graph H has at least three edges, then s-Hom(H) is NP-complete; it is polynomial-time otherwise.…”
Section: S-hom(h)mentioning
confidence: 99%
See 4 more Smart Citations
“…Extending the Hell-Nešetřil dichotomy [27] for Hom(H) for 1-edge-coloured graph problems, a complexity dichotomy for s-Hom(H) problems was proved in the papers [7,10]. The authors showed that if the s-core of a signed graph H has at least three edges, then s-Hom(H) is NP-complete; it is polynomial-time otherwise.…”
Section: S-hom(h)mentioning
confidence: 99%
“…An interesting case is the one when H = (C k , σ) is a cycle (k ≥ 3). If H is switching-equivalent either to an all-positive C k , or to an all-negative C k , then the complexity of s-Hom(H) and Planar s-Hom(H) are the same as the ones of Hom(C k ) and Planar Hom(C k ), respectively [7]. When k is odd, one of these two cases holds, and thus by the results of [25,33], in that case Planar s-Hom(H) is NP-complete.…”
Section: Planar S-hom(h)mentioning
confidence: 99%
See 3 more Smart Citations